From Incunabula to Book History: Ethiopia, Eritrea and the Search for their Printed Past - Zaccaria, Massimo (Aethiopica, 2021)
The history of the printed book in Africa is a relatively new line of inquiry. One of the most challenging issues confronting its practitioners will be to produce authoritative and comprehensive records of the national output of African countries, an essential prerequisite before venturing into more complex analysis. In this panorama, Eritrea and Ethiopia seem to represent two happy exceptions: the pioneering work of Ḫǝruy Wäldä Śǝllase, Stephen Wright’s Ethiopian Incunabula and then the supplements by Stefan Strelcyn, Osvaldo Raineri, and Kibrom Tseggai have allowed for the reconstruction of large sections of the print production of the two countries. This article maps out the cultural and political context in which the attention for Ethiopian incunabula emerged and traces the stages of the collective effort that has allowed the preservation of the traces of the early printed documentation in Eritrea and Ethiopia. The article argues that there are still significant margins of improvement in the retrospective coverage of the history of the printed book in Africa, especially since the arrival of digital technologies and the Internet that have offered a very effective set of tools for solving some of the problems that have plagued African retrospective national bibliographies since their inception.